Efficient development and Characterisation of Asp-AuNPs based colorimetric sensor for the detection of Ag(I) from real water samples. Issue 16 (16th December 2022) - Memon, Safia Sanam; Sirajuddin; Memon, Shahabuddin; Kumar, Ameet; Memon, Nusrat Shahab
ABSTRACT: In this work, we develop an effective and efficient method for the preparation of gold nanoparticles (AuNPs). In this method, we used acetylsalicylic acid named aspirin (Asp) as a reducing agent. However, there is no need for any stabiliser to stabilise the reaction. The prepared nanoparticles were characterised by using FT-IR, UV-Visible, AFM, and XRD. These Asp-AuNPs nanoparticles were applied for the sensitive and selective determination of silver ions (Ag + ). The estimated average size of gold nanoparticles was 33 nm. The sensor responds in the linear range of 0.002–0.015 µM. The sensor response towards other metals i.e. Li +, Cu 2+, Ni 2+, Co 2+, Pb 2+, Zn 2+, Fe 2+, Cr 3+ and As 3+ was obtained negligible. The limit of detection (LOD) of the prepared sensor was found up to 0.046 nM. The prepared colorimetric sensor was effectively applied to determine Ag + ions in real water samples obtained from jewellery shops from different places of Hyderabad, Sindh Pakistan.